Architectural and catalytic aspects of designer materials built using metalloligands of pyridine-2, 6-dicarboxamide based ligands. Issue 42 (21st October 2020) - Pachisia, Sanya; Gupta, Rajeev
Abstract : This perspective presents the design, structural and catalytic aspects of discrete complexes as well as multi-dimensional coordination polymers constructed using assorted metalloligands offering various appended functional groups. Abstract : This perspective presents the design, synthesis and crystal structures of a large number of architectures constructed using assorted metalloligands of pyridine-2, 6-dicarboxamide based ligands. The metalloligands offered various appended functional groups, whereas design strategies included varying both their position and number. A combination of these parameters resulted in the development of assorted architectures including discrete trinuclear and tetranuclear complexes as well as 1D/2D/3D coordination polymers. The metalloligand strategy not only assisted in the construction of ordered crystalline materials with varied dimensionalities but also judiciously allowed the incorporation of Lewis acidic and redox-active secondary metals in the resultant architectures. As a result, such designer architectures illustrated their noteworthy role both as homogenous and heterogeneous catalysts in different organic transformation reactions.